THE EFFECT OF SCHOOL LEADERSHIP AND QUALITY ASSURANCE ON THE PERFORMANCE OF TEACHERS ELEMENTARY SCHOOL IN DISTRICT PADANGSIDIMPUAN HUTAIMBARU - MONICA THERESIA; RONALD FRANSYAIGU; RUSDINAL RUSDINAL; SUFYARMA MASIDIN (CV KULTURA DIGITAL MEDIA, 2020)
The purpose of this study was to describe and analyze the effects of: 1) principal leadership on teacher performance, 2) quality assurance on teacher performance and 3) principal leadership and quality assurance simultaneously on the performance of public elementary school teachers in Padangsidimpuan Hutaimbaru District. This type of research is quantitative using the ex post facto method. The sample used the Slovin formula as many as 101 of the 136 teachers who taught at SD Negeri in Padangsidimpuan Hutaimbaru District. Data obtained through questionnaires and documentation, then analyzed using correlational and regression techniques both simple and multiple. Hypothesis testing is done by using Product Moment correlation and multiple correlation, which previously tested for normality and homogeneity. The results of the study are as follows: 1) there is a positive influence between principal leadership on teacher performance, meaning that the better the teacher's perception of the principal's leadership, the better the performance, 2) there is a positive influence between quality assurance on teacher performance, it contains meaning that the better the teacher's perception of quality assurance, the better the performance, 3) there is a positive and significant influence between principal leadership and quality assurance on teacher performance, meaning that the better the teacher's perception of the principal's leadership and quality assurance, the better good performance too. Suggestions are conveyed from the results of this study, especially to teachers in order to improve and create good teacher performance. Meanwhile, the principal should exercise leadership well using a kinship approach in order to create the desired quality assurance.